A STUDY ON THE FINANCIAL PERFORMANCE OF NLC INDIA LIMITED - MAHESWRI, M. (International Journal of Psychosocial Rehabilitation, 2020)
-- The study is an attempt to find the financial performance of NLC India Limited. In this study, two objectives were framed and this two were concluded in conclusion part. The key variables of analysis were sales, other income, expenditure, operating expenses, depreciation, finance cost, and tax. The results revealed that the profit was gradually increased and it leads to increased provision for and dividend payout. The ROCE value was slight fluctuating due to environmental or non-accounting factors during the study period. The gross block values, net block values, depreciation values and investments values of NLC India Limited were gradually increased during the study period.